The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1117/12.532524
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic write-once disc with quadruple recording layers for Blu-ray Disc system

Abstract: The optical disc with larger capacity and higher speed data recording rate will be required in coming broadband network society. We have developed the inorganic write-once disc with quadruple recording layers for the blu-ray disc system. We obtained the reflectivity of more than 5 % and a jitter value of less than 10% for each recording layer. As a result, we proved the possibility of 100 GB user capacity of 120 mm diameter size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 3 publications
1
17
0
Order By: Relevance
“…The calculated reflectivity for several numbers of layers is summarized in Table 1. These values are consistent with the previous reports of multi-layer discs [1][2][3][4][5][6][7].…”
Section: Methodssupporting
confidence: 94%
See 1 more Smart Citation
“…The calculated reflectivity for several numbers of layers is summarized in Table 1. These values are consistent with the previous reports of multi-layer discs [1][2][3][4][5][6][7].…”
Section: Methodssupporting
confidence: 94%
“…Currently, write-once discs with up to six layers (200 Gbytes) and read-only memory (ROM) discs up to twenty-layers (500 Gbytes) have been demonstrated [1][2][3][4][5][6][7]. However, multilayer recording suffers from a serious decrease in signal level, which causes an insufficient signal-to-noise ratio (SNR).…”
Section: Introductionmentioning
confidence: 99%
“…Mishima, et al reported a write-once type quadrilayer recordable disc employing a high-transmissive ZnSiMg-O-S recording material for intervening layers. 5 Their quadrilayer structure, in contrast, was formed by spin-coated resin spacers.…”
Section: Introductionmentioning
confidence: 98%
“…These days, many impressive results of technical candidates for the next-generation optical discs have been reported in this field. The technical candidates include volumetric storage technology, [1][2][3][4][5][6] near-field technology, [7][8][9][10][11][12][13] and multilayer technology, [14][15][16][17][18][19][20] which is a volumetric storage technology. Among them, multilayer technology has a lot of advantages such as storage capacity, backward compatibility, and system practicability, and so on.…”
Section: Introductionmentioning
confidence: 99%